Understanding low sensitivity of community‐based HIV rapid testing: experiences from the HPTN 071 (PopART) trial in Zambia and South Africa. (29th August 2017) - Bock, Peter; Phiri, Comfort; Piwowar‐Manning, Estelle; Kosloff, Barry; Mandla, Nomtha; Young, Alicia; James, Anelet; Schaap, Ab; Scheepers, Michelle; Donnell, Deborah; Griffith, Sam; El‐Sadr, Wafaa; et al.
Abstract: Introduction : Population‐wide HIV testing services (HTS) must be delivered in order to achieve universal antiretroviral treatment (ART) coverage. To accurately deliver HTS at such scale, non‐facility‐based HIV point‐of‐care testing (HIV‐POCT) is necessary but requires rigorous quality assurance (QA). This study assessed the performance of community‐wide HTS in Zambia and South Africa (SA) as part of the HPTN 071 (PopART) study and explores the impact of quality improvement interventions on HTS performance. Methods : Between 2014 and 2016, HIV‐POCT was undertaken within households both as part of the randomly selected HPTN 071 research cohort (Population Cohort [PC]) and as part of the intervention provided by community HIV‐care providers. HIV‐POCT followed national algorithms in both countries. Consenting PC participants provided a venous blood sample in addition to being offered HIV‐POCT. We compared results obtained in the PC using a laboratory‐based gold standard (GS) testing algorithm and HIV‐POCT. Comprehensive QA mechanisms were put in place to support the community‐wide testing. Participants who were identified as having a false negative or false positive HIV rapid test were revisited and offered retesting. Results : We initially observed poor sensitivity (45–54%, 95% confidence interval [CI] 31–69) of HIV‐POCT in the PC in SA compared to sensitivity in Zambia for the same time period of 95.8% (95% CI 93–98). In both countries, specificity of HIV‐POCT was >98%. With enhanced QA interventions and adoption of the same HIV‐POCT algorithm, sensitivity in SA improved to a similar level as in Zambia. Conclusions : This is one of the first reports of HIV‐POCT performance during wide‐scale delivery of HTS compared to a GS laboratory algorithm. HIV‐POCT in a real‐world setting had a lower sensitivity than anticipated. Appropriate choice of HIV‐POCT algorithms, intensive training and supervision, and robust QA mechanisms are necessary to optimize HIV‐POCT test performance when testing is delivered at a community level. HIV‐POCT in clients who did not disclose that they were on ART may have contributed to false negative HIV‐POCT results and should be the topic of future research.